Desenvolvimento e validação de metodologia para avaliação de fosfato de sitagliptina - Ravanello, Aline (2010)
Sitagliptin Phosphate is an oral anti-hyperglycemic belonging to a new class of medicine used in type 2 diabetes treatment, the dipeptidyl dipetidase -4 (DPP-4) enzyme inhibitors. This drug besides being safe and tolerated, stimulates the insulin secretion, lowers the glucagon release, delays the gastric emptiness and increases beta cells life. It is commercially available as covered pills. So far, there is not any monograph to analyze sitagliptin phosphate in its pharmaceutical form. In this work some methods were developed and validated to evaluate and quantify the drug. The methods used to quantify it were high pressure efficiency liquid chromatography (HPLC) and spectrophotometry. The system through HPLC was carried out in room temperature and in an isocratic way with Phenomenex C 18 (15 cm x 4.6mm) reverse phase column and the mobile phase composed by 0.025M pH 6.8 phosphate buffer: acetronytril (60:40, v/v) with 0.8 mL /min. flow. The detection was accomplished in PDA in 267nm. With the spectrophotometric method the solvent used was HCI 0.01N and its detection was accomplished in 267nm wave length. The methods show a good linearity, precision and accuracy and having no significant difference between them. Later, some dissolution tests were carried out with different bacthes of drug and with similar results.